2008
DOI: 10.1080/09603100701604225
|View full text |Cite
|
Sign up to set email alerts
|

Estimating stock market volatility using asymmetric GARCH models

Abstract: A comprehensive empirical analysis of the mean return and conditional variance of Tel Aviv Stock Exchange (TASE) indices is performed using various GARCH models. The prediction performance of these conditional changing variance models is compared to newer asymmetric GJR and APARCH models. We also quantify the day-of-the-week effect and the leverage effect and test for asymmetric volatility. Our results show that the asymmetric GARCH model with fat-tailed densities improves overall estimation for measuring cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(140 citation statements)
references
References 29 publications
(28 reference statements)
10
104
0
5
Order By: Relevance
“…The Asymmetric Power ARCH (APARCH henceforth) model by DingGranger -Engle (1993) is probably one of the most interesting ARCH type models 1 . It can be expressed as:…”
Section: Methodology -Garch Class Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Asymmetric Power ARCH (APARCH henceforth) model by DingGranger -Engle (1993) is probably one of the most interesting ARCH type models 1 . It can be expressed as:…”
Section: Methodology -Garch Class Modelsmentioning
confidence: 99%
“…As the estimated coefficients 1  and 1  shown in the Table 2 are both negative, The next step in our analysis was the calculation of NIC for models from the crisis dataset. As in the case of GARCH and TGARCH models we have used ARCH order of 2, the news impact curve changes to news impact surface.…”
Section: Garch Egarch Tgarchmentioning
confidence: 99%
“…where K(·) and B are defined respectively in (1) and (3). We see that all the moments can be expressed simply and conveniently in terms of the Gamma function.…”
Section: Stochastic Representation Moments and Implications Of Paramentioning
confidence: 99%
“…For example, Bollerslev (1987) used the Student-t to model the distribution of foreign exchange rate returns; Mittnik, Rachev and Paolella (1998) fitted a return distribution using a number of parametric distributions including Student-t, and found that the partially asymmetric Weibull, Student-t and the asymmetric stable distributions provide the best fit according to various measures. Recent applications include Alberg et al (2008) and Franses et al (2008). Hansen (1994) was the first to consider a skewed Student's t distribution to model skewness in conditional distributions of financial returns.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it helps to obtain more robust estimates because EGARCH and APARCH models' structure has some differences (Karanasos and Kim, 2003). Particularly, such a method was used for model testing on Thai (Kongprajya, 2010) and Israeli stock markets (Alberg et al, 2008). In addition, this model enables to check some other parameters of EGARCH and GARCH models, such as: effect of stability of shocks' impact on volatility and presence of risk premium.…”
Section: Methodsmentioning
confidence: 99%